UPAYA PENINGKATAN PEMAHAMAN WAWASAN NUSANTARA SEBAGAI ALAT PEMERSATU BANGSA - hilmi ana utami; Novia Wahyu Wardhani (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2023)
Along with the development of increasingly advanced technology, the sense of nationalism of the millennial generation is decreasing because it is influenced by western culture. To overcome this, it is necessary to have a solution. To overcome this, Indonesian citizens, especially the millennial generation, need to be given more understanding of the archipelago's insight by means of Citizenship Education at every level of education, even up to universities in which they learn about the archipelago. The role of insight into the archipelago is as a guide, motivation, encouragement, and signs in finding all policies, decisions, actions, and actions for state administrators at the central and regional levels as well as for all Indonesian people in the life of society, nation and state. In addition, it can shape the nation's mental attitude which includes creativity, taste and initiative in an integrated manner. The insight of the archipelago as a unifying tool for the nation is proven in its function of fostering a sense of nationalism based on socio-cultural diversity and the geographical location of the Unitary State of the Republic of Indonesia. With an increased understanding of the archipelago's insight, millennials are more tolerant and appreciate the services of the heroes.